(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
This article explores shadow theater as a playful practice in early childhood education, highlighting its role in stimulating children’s play, creativity and development. Through artistic practices, we seek to promote individual expression, autonomy and imagination. Shadow theater, as a pedagogical approach, offers experiences that involve the manipulation of light and shadow, favoring integral development. The study also reports three moments of the practical application of this technique, demonstrating its effectiveness in early childhood education and its value as a resource to stimulate imagination and free expression.